Effect of morphology and defectiveness of graphene-related materials on the electrical and thermal conductivity of their polymer nanocomposites. (12th October 2016) - Colonna, S.; Monticelli, O.; Gomez, J.; Novara, C.; Saracco, G.; Fina, A.
Abstract: In this work, electrically and thermally conductive poly (butylene terephthalate) nanocomposites were prepared by in-situ ring-opening polymerization of cyclic butylene terephthalate (CBT) in presence of a tin-based catalyst. One type of graphite nanoplatelets (GNP) and two different grades of reduced graphene oxide (rGO) were used. Furthermore, high temperature annealing treatment under vacuum at 1700 °C was carried out on both RGO to reduce their defectiveness and study the correlation between the electrical/thermal properties of the nanocomposites and the nanoflakes structure/defectiveness. The morphology and quality of the nanomaterials were investigated by means of electron microscopy, x-ray photoelectron spectroscopy, thermogravimetry and Raman spectroscopy. Thermal, mechanical and electrical properties of the nanocomposites were investigated by means of rheology, dynamic mechanical thermal analysis, volumetric resistivity and thermal conductivity measurements. Physical properties of nanocomposites were correlated with the structure and defectiveness of nanoflakes, evidencing a strong dependence of properties on nanoflakes structure and defectiveness. In particular, a significant enhancement of both thermal and electrical conductivities was demonstrated upon the reduction of nanoflakes defectiveness. Graphical abstract: Highlights: Thermally conductive PBT nanocomposites prepared by ring-opening polymerization. First-time evidences of rGO defectiveness vs. nanocomposite conductivity. Low defectiveness of carbon nanoflakes: a must for highly conductive nanocomposites. High temperature annealing suitable to reduce carbon nanoflakes defectiveness.